Proposed Ninth Five Year Plan 1997 - 2002 Administration of Andaman and Nicobar Islands - Planning Commission (Planning Commission, 1997)
The process of infrastructure development was started only from 6th plan and therefore, a lot has to be done to restore the regional imbalance created due to inadequate funding in this sector. Even during the 6th, 7th & 8th Plan more or less 40% of the plan funds were spend on shipping which did not lead to any infrastructure development in the territory. Purchase of ships does not add to the basic infrastructure capacity of the lands which require roads, power, bridges, schools, hospitals etc. The result is that even at the end of the 8th Plan we have only 866 kms of roads. The installed power capacity is only 29.829 MW. There are only five medium size industries of which four are timber based which is a depleting resource.
Administration of Andaman and Nicobar